Laser-Assisted In Situ Keratomileusis Surgery on a Patient with Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disease or Neuromyelitis Optica Spectrum Disorder - Majid Moshirfar; Duncan J. Williams; Melody Ziari; Meagan D. Seay; Yasmyne C. Ronquillo (Case Reports in Ophthalmological Medicine)
Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) and neuromyelitis optica spectrum disorder (NMOSD) are rare central demyelinating diseases that may affect refractive surgery outcomes. Optic neuritis and brainstem syndromes affecting cranial nerves are particularly relevant to corneal refractive surgery (CRS), such as laser-assisted in situ keratomileusis (LASIK), photorefractive keratectomy, or small incision lenticule extraction. There is currently no existing literature concerning the outcomes of CRS in patients with MOGAD or NMOSD. This article reports the clinical outcome of a MOGAD patient who underwent LASIK.